Examination of the effect of pelleted poultry manure products on a sunflower test plant in a laboratory model experiment - Gorliczay, Edit; Szöllősi, Nikolett; Kiss, Nikolett Éva; Tóth, Florence; Tamás, János; Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2021)
Sunflower (Helianthus annuus L.) is one of the most important oil plants in Hungary, with a sown area of more than 627.000 ha in 2019. Sunflower cultivation is primarily important for use in the oil industry, but its role in feed and beekeeping cannot be neglected either. Sunflower adapts well to different production areas in terms of soil demand, yet, as important fact, it must be grown on soils with poorer conditions with intensive nutrient replenishment. From the agri-environmental point of view, in addition to the use of pelleted poultry manure products, which are also new to the consumer market, is of paramount importance. Their advantages include a wide range of nutrients as well as a soil structure improving effect. In our research, we investigated the starter effect of pelleted poultry manure products applied at different doses (200 kg ha-1 and 400 kg ha-1) on sandy soil with humus using a sunflower plant. The aim of our research to investigate the effect of using pelleted fertilizer products as starter fertilizers on sunflower plant germination, and investigate the effect of poultry manure products on soils.Based on our results, it can be stated that the pigment content (chlorophyll and carotenoid content) was positively influenced by the higher dose treatments (400 kg ha-1), thus increasing the photosynthetically active leaf area. Compared to the control, the carotenoid content in the test plants of the treatments increased, and the differences of this treatment proved to be significant (p